2004
DOI: 10.1074/jbc.m406002200
|View full text |Cite
|
Sign up to set email alerts
|

Activated Polyamine Catabolism Depletes Acetyl-CoA Pools and Suppresses Prostate Tumor Growth in TRAMP Mice

Abstract: The enzyme spermidine/spermine N 1 -acetyltransferase (SSAT) regulates the catabolism and export of intracellular polyamines. We have previously shown that activation of polyamine catabolism by conditional overexpression of SSAT has antiproliferative consequences in LNCaP prostate carcinoma cells. Growth inhibition was causally linked to high metabolic flux arising from a compensatory increase in polyamine biosynthesis. Here we examined the in vivo consequences of SSAT overexpression in a mouse model genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
74
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 39 publications
(50 reference statements)
10
74
1
1
Order By: Relevance
“…Although the basis for this phenomenon is unknown, it is likely manifested during gestation because there were no noticeable increases in postnatal mortality. Normal Mendelian segregation of genotypes was observed previously in a cross of SSAT transgenic and TRAMP mice (13,19). The deficiency of MIN/SSAT-tg progeny in the current cross may be related to the report of Jacoby et al (26,27), who observed that treatment with the ODC inhibitor a-difluoromethylornithine during embryonic development is selectively lethal to fetuses bearing a heterozygous mutation in the Apc gene.…”
Section: Ssatsupporting
confidence: 74%
See 2 more Smart Citations
“…Although the basis for this phenomenon is unknown, it is likely manifested during gestation because there were no noticeable increases in postnatal mortality. Normal Mendelian segregation of genotypes was observed previously in a cross of SSAT transgenic and TRAMP mice (13,19). The deficiency of MIN/SSAT-tg progeny in the current cross may be related to the report of Jacoby et al (26,27), who observed that treatment with the ODC inhibitor a-difluoromethylornithine during embryonic development is selectively lethal to fetuses bearing a heterozygous mutation in the Apc gene.…”
Section: Ssatsupporting
confidence: 74%
“…This provocative finding suggests quite clearly that high levels of SSAT expression can exert tumor-suppressive effects. However, in contrast to expectations, polyamine pools were not significantly depleted by SSAT in either LNCaP cells or in prostate tumors of TRAMP mice (13,19). Rather, the antitumor effect seems to be directly related to a compensatory up-regulation of polyamine biosynthesis in response to SSAT overproduction.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Gupta et al (18) showed marked reduction in weight and volume of the prostate as well as metastasis in the group treated with 1% DFMO. Another group reported on the manipulation of polyamines in the transgenic adenocarcinoma mouse prostate model by overexpression of spermidine/spermine N1-acetyltransferase, which regulates the catabolism and export of intracellular polyamines (19). The transgenic adenocarcinoma mouse prostate/spermidine/spermine N 1-acetyltransferase animals had smaller weights of their prostates at 30 and 36 weeks and better histologic scores.…”
Section: Introductionmentioning
confidence: 99%
“…The net cytosolic spermidine content further depends on its catabolism, which is mainly driven by acetylation and subsequent oxidation [2931], but also on its uptake from the extracellular space and its excretion by the cell. This may be mediated by membrane transporters such as the ones operating in yeast and bacteria [32], but could also involve endocytosis/exocytosis processes.…”
mentioning
confidence: 99%